Developing Youth Leaders: Institutional Social Bonding Influence and Positive Youth Development - Mohamed, Nor Hidayah; Hassan, Siti Azura Abu (Archives of Business Research, 2020)
The purpose of this research is to identify the factors contribute to Positive Youth Development (PYD) among Community Colleges’ students comprising the 5Cs namely Competence, Confidence, Character, Connection and Caring and Compassion. Moreover, the study highlighted the domains from institutional social bonding that might influence the development of youth at Community Colleges to be a positive leader. The Ecology of Human Development theory, the Developmental Science theory and Social Bonding Theory provide the foundation for this area of study. The framework form Institutional social bonding and 5C’s of PYD elements are recommended. Leadership and PYD are related theoretical based approach in youth development. A youth leadership potential can be unleashed through the development of the 5Cs that lead to positive outcomes. Social bonding with school or institution will nurture and develop the positive characteristics of a leader through involvement, attachment, commitment and trust between both elements.